Juniper QFX5100 series a comprehensive guide to building next-generation networks - Hanks, Douglas Richard (O'Reilly Media, 2015)
Ideal for network engineers involved in building a data center, this practical guide provides a comprehensive and technical deep-dive into the new Juniper QFX5100 switching family.